Comparative Analysis of Early Childhood Education in Australia and Turkey - Ahi, Berat; Kildan, A. Oguzhan (Elsevier BV, 2013)
AbstractThe purpose of this article is to compare the historical development and the current situation of early childhood education in Australia. The main objective of the study is to form a conclusion about early childhood education in Turkey, drawing on the Australian example. Campaigns that planned and developed early childhood education began under the leadership of women. The active participation of women in daily life was as a key development that highlighted the importance of early childhood education. Campaigns for preschool education began later in Turkey compared to those in Australia. Today, there are similarities, in terms of philosophy, of both the programme and structure of preschool education in each country. Preschool education is not compulsory in either country. There are play- and child-oriented programmes. To involve families, the HIPPY is applied in Australia, and institution-centred family education is carried out in Turkey.
Keywords: Early childhood education; Turkish early childhood education system.; Australian early childhood education system; early childhood education system; 4. Education; 10. No inequality